Jóvenes transgresores de la ley penal: representación, discurso e identidad - Wilson Herney Mellizo Rojas (Cambios y Permanencias, 2017)
The article contributes to the study of representations about young people and processes of juvenile subjectivation of boyswho violate criminal law related to reeducation programs in Colombia. Ppresentsresults of a research in the field of cultural studies, organized intothree parts: a context of the dominant imaginaries about young offenders of the criminal law in our country; then introduces the central nucleus of the article: the systems of representations that are built on reeducation programs for young people, and ends with reflections on the practices of education and care.